IMPLEMENTATION OF A LOVE-BASED CURRICULUM IN THE FIQH SUBJECT AT THE PRIVATE MTS DARUL ULUM BUDI AGUNG MEDAN - Patimah Nurun Marpaung; Zaini Dahlan (Jurnal Asy-Syukriyyah, 2026)
This study examines the implementation of a love-based curriculum in Islamic Jurisprudence (Fiqh) learning at Darul Ulum Budi Agung Private Islamic Junior High School. The research aims to describe strategies for integrating compassion values into the learning process and analyze their impact on students' behavior and learning motivation. A qualitative descriptive approach was employed through participatory observation, in-depth interviews with the principal, Fiqh teachers, and students, as well as documentation studies. The findings reveal that the curriculum was implemented by creating a warm classroom environment, using polite and empathetic communication, and applying persuasive guidance in religious practices. The study also found improvements in students' positive attitudes, discipline, and motivation to learn. These findings highlight the importance of a humanistic approach in Fiqh education to foster inclusive religious character development rooted in compassion and mutual respect.